Species diversity and temporal stabilization of root productivity of tropical grassland to nitrogen application - Preeti Verma (Elsevier, 2021)
Alarming rate of atmospheric nitrogen (N) deposition through massive uses of N-fertilizers has become a major issue for the sustainability of ecosystem structure and function. N manipulative studies in temperate regions have yielded debated responses of species diversity, root primary productivity, temporal stability of root primary productivity to the increasing N-inputs and these structural and functional attributes of the ecosystem may or may not be interlinked. There is a lacuna of such studies from tropical ecosystems and they are totally missing from the tropical grasslands which are receiving very high rate of N-fertilization and are facing unprecedented loss of biodiversity. The objectives of the present study were to explore the responses of diversity, root primary productivity, stability of root primary productivity (sustainable functioning of ecosystem) and their relationships to six levels of N-fertilization. Also, we tried to find out the optimal level of N-fertilization for sustainable functioning of the tropical grassland and to reveal the mechanism behind it. Within the experimental grassland, 72 1 × 1 m plots with 6 N-input levels (0, 30, 60, 90, 120 and 150 Kg N ha−1yr−1) each having 12 replicates, were established in 2013. For three consecutive years starting from 2013 to 2016, urea as a source of N was applied to the plots for simulating N-deposition. Data on individuals and root biomass of each species were seasonally recorded and statistically analysed. The diversity, root primary productivity and its stability significantly varied and quadratically responded to the N-fertilization doses. 90 Kg ha−1yr−1N fertilization yielded maximum primary productivity and its stability, whereas 60 Kg ha−1yr−1N-fertilization resulted in maximum diversity. Thus a moderate level of N application (90 kg ha−1 yr−1) appeared to be an optimum dose for stable functioning of the tropical grassland. Doses of N-fertilization beyond 90 Kg ha−1 yr−1 inhibited the sustainable ecosystem functioning because the substantially high N-fertilization resulted in increased soil acidity which enhanced soil-Al toxicity to the plant roots and loss of diversity. Nevertheless, further longer-term study could be needed for a more robust conclusion.